Systematic Review and Meta‐analysis: Effectiveness of Corticosteroids in Treating Adults With Acute Vestibular Neuritis. (2nd February 2021) - Leong, Kai‐Jing; Lau, Timothy; Stewart, Vicky; Canetti, Elisa F. D.
Abstract : Objectives: To determine whether steroids are effective in treating adults with acute vestibular neuritis. Data Sources: PubMed, Embase, CINAHL, Cochrane CENTRAL, Web of Science, CAB Abstract, ICTRP, LILACS, PEDRO, ClinicalTrials.Gov, Google Scholar, NARIC, and OT Seeker. Review Methods: A systematic review was undertaken for articles reporting subjective and/or objective outcomes of corticosteroids in adults with acute vestibular neuritis between December 2010 and October 2019. Reports of patient recovery from clinical vestibular outcomes at various time points and adverse effects from corticosteroids were of interest. Statistical analysis included qualitative and quantitative assessments. A limited meta‐analysis of the data was performed through a random effects model. Results: Eight studies met the criteria, and 6 were included in the meta‐analysis. No significant differences between the groups (corticosteroid vs placebo, corticosteroid vs vestibular exercise, or corticosteroid vs combination of vestibular exercise and corticosteroid) were reported in the proportion of patients with complete recovery at 1, 6, and 12 months. The corticosteroid group had significantly better caloric recover at 1 month (95% CI, –16.33 to –0.32); however, there was no significant difference to the overall effect between the groups across 12 months. Subjective recovery did not differ between the groups. Five of the 8 studies reported on adverse effects from corticosteroids. Conclusion: There is insufficient evidence to support the use of corticosteroids in managing acute vestibular neuritis in adults. At present, corticosteroids appear to have short‐term benefits in canal paresis but no long‐term benefits in canal paresis and symptomatic recovery. Future studies should consider including a wider variety of clinical vestibular tests and frequent acute follow‐ups to monitor the effects of corticosteroids.